Network structure and molecular mechanisms of food gels viewed from macroscopic, microscopic and molecular levels - Descallar, Faith Bernadette A.; Yang, Xi; Geonzon, Lester C.; Matsukawa, Shingo (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
This article reviews different studies on the gelation mechanisms and network structural characteristics in polysaccharide gels at the different length scales of observation: macroscopic, microscopic, and molecular. Rheological and micro-DSC (Differential Scanning Calorimetry) measurements represent the macroscopic viewpoints on the gelation of pure kappa-carrageenan (KC), iota-carrageenan (IC) and KC/IC mixtures. Microscopic rheological properties observed using particle tracking experiments have been used to elucidate the formation of heterogeneous networks of KC-rich and IC-rich domains in mixed KC/IC gels, and facilitate observations of their aging process. Nuclear magnetic resonance (NMR) relaxation time measurements provide information on the tumbling motion and local mobility; these molecular-level experiments are presented for agar, agarose, native gellan and deacylated gellan chains. NMR diffusion measurements of gelling and probe polymers give insights into the conformational changes, aggregation and network formation, and aging mechanisms, and are presented for all studied polysaccharides.